Trailing Tennessee [book club bag] - Mimms, Cory Wheeler (Craigmore, 2013)
After his father's sudden death, fourteen-year-old Eli Sutton begins hiking the Appalachian Trail, a dangerous trek on which he is pursued by park rangers and spirits, to fulfill his dream of reaching Mount Katahdin and carving his initials on the same tree as his father and grandfather.